DA'I WALAKEDU: THE DILEMMA OF DA’WAH WAGES AT HAMZAH YUNUS MUHAMMADIYAH ISLAMIC BOARDING SCHOOL KUOK – A STUDY ON THE CONCEPT OF AL-UJRAH 'ALA AL-THA'AH - Desteny Layla; Hamda Sulfinadia; Efrinaldi Efrinaldi (UIN Siber Syekh Nurjati Cirebon, 2024)
This research focuses on the dilemma faced by da'i in determining da'wah rates, which has led to the emergence of the term da'i walakedu in Indonesia. The study aims to analyze how Islam views the concept of al-ujrah ala al-tha'ah in relation to preachers who accept wages, either voluntarily or by setting specific rates. This research employs a field research methodology, using primary data collected through questionnaires. The sample for this study consists of seven teachers who also serve as preachers at the Mahmud Yunus Muhammadiyah Kuok Islamic Boarding School in Kampar.The findings reveal differing opinions among scholars regarding wages for preaching. According to the concept of al-ujrah ala al-tha'ah, the wages accepted by preachers are not considered payment for the knowledge imparted but are viewed as a form of assistance in obedience, which is regarded as an act of worship. Therefore, taking wages for preaching is permissible, provided that excessively high rates are not set. This dilemma is evident among the preachers at the Hamzah Yunus Muhammadiyah Kuok Islamic Boarding School. The wages they receive for preaching do not always carry a negative connotation, as these earnings are not used as a means of accumulating wealth. Instead, the wages are utilized for personal and family needs and are often allocated to help those in need. As a result, the preachers at the Islamic boarding school cannot be classified as da'i walakedu (commercial preachers).